Dampak Influencer Marketing Dan Online Customer Reviews Terhadap Online Purchase Decisions Dimediasi Oleh Customer Trust - Nyoman Udayana, Ida Bagus; Hanafi, Faturrahman; Hatmanti Hutami, Lusia Tria (Universitas Hamzanwadi, 2024)
This study specifically targets the individuals who utilize the Shopee marketplace platform inside the city of Yogyakarta. The objective of this study is to examine the impact of customer reviews and online influencer marketing on online purchasing decisions, with customer trust playing a mediating role. The data collection instrument employed was a questionnaire created using Google Forms, and a total of 120 participants were chosen by purposive selection approaches. Afterwards, the data were analyzed using the SPSS version 25 software. This analysis incorporates the utilization of Sobel testing, R2 or coefficient of determination assessment, t-test examination, F-test examination, verification of traditional assumptions, and evaluation of Multiple Linear Regression. The study's findings suggest that influencer marketing positively influences consumer trust. Additionally, online customer reviews have a key role in shaping consumer trust, while consumer confidence has a favorable and substantial impact on online purchase decisions. Nevertheless, neither influencer marketing nor online customer evaluations have a direct influence on consumers' decisions to make online purchases